Experimental and numerical studies on flow from axisymmetric nozzle flow with sudden expansion for Mach 3.0 using CFD - Quadros, Jaimon Dennis; Khan, Sher Afghan; A. J., Antony; Vas, Jolene S. (ISET 2016, 2016)
Researches over the recent past in the field of aerodynamic vehicles have been concerned with the problem of flow separation over its base which has lead to the formation of low pressure circulation region. This pressure is found to be noticeably lower than the free stream atmospheric pressure. Base drag due to such pressure differences can be up to twothirds of the total drag and is principally dictated by base pressure. The present study aims to conduct experiments in order to study the variation of base pressure from an axisymmetric nozzle exit of 10mm diameter. Area ratio i.e. ratio of area of suddenly expanded duct to nozzle exit area considered in this particular study is 4.84. The fundamental control parameters considered in the study are the nozzle pressure ratio (NPR) and length-to-diameter (L/D) ratio which apparently are the inertia and geometric parameters respectively. The tests are conducted for NPR’s ranging from 3 to 11 in steps of 2. Accordingly L/D ratio was considered from 10 to 1 where tests were conducted for L/D 10, 9, 8, 7, 6, 5, 4, 3, 2 and 1. The results showed that for increase in the NPR values once the flow is attached to the duct, the base pressure progressively decreased. Wall pressure distribution throughout the enlarged duct is also studied to understand the oscillatory nature of flow. This work also proposes an effective numerical model for base pressure using Computational Fluid Dynamics (CFD). The computational/numerical model of the axisymmetric nozzle and the enlarged duct was constructed using ANSYS Fluent which is the CFD solver and employed in the present work. Numerical iterations were completed, and the detailed values for base pressure are analyzed. The numerical results were found to agree well with the experimental ones.